Toxicity caused by para-substituted phenols on Tetrahymena pyriformis: The structure-activity relationships - Jäntschi, Lorentz; Popescu, Violeta; Bolboacă, Sorana D. (Electronic Journal of Biotechnology, 2008)
The toxicity of thirty para-substituted phenols on Tetrahymena pyriformis was modelled using an original methodology that uses the complex structural information of the compounds. Two models were built. The methodology allows atomic properties to be assigned to toxicity based on the selection of pairs of descriptors from the entire family, which is called Molecular Descriptors Family (MDF). One model has two independent structural descriptors and the other has four. The model with four descriptors proved to have high estimated and predictive abilities (over 97% of toxicity could be explained by structural information). The partial charge distribution by bonds (molecular topology) and space (molecular geometry) interaction proved to be related with the toxicity of para-substituted phenols on Tetrahymena pyriformis. The predictive ability of the model was tested by using the following methods: the cross-validation leave-one-out and the training versus test experiments. The comparisons among the models were performed using the correlated correlations method. The embedding of the complex information from the structure using MDF methodology can lead to further investigations of the mechanism of chemicals toxicity on Tetrahymena pyriformis.